Formation of ice eddies in subglacial mountain valleys. Issue 9 (5th September 2017) - Meyer, Colin R.; Creyts, Timothy T.
Abstract: Radar data from both Greenland and Antarctica show folds and other disruptions to the stratigraphy of the deep ice. The mechanisms by which stratigraphy deforms are related to the interplay between ice flow and topography. Here we show that when ice flows across valleys or overdeepenings, viscous overturnings called Moffatt eddies can develop. At the base of a subglacial valley, the shear on the valley sidewalls is transferred through the ice, forcing the ice to overturn. To understand the formation of these eddies, we numerically solve the non‐Newtonian Stokes equations with a Glen's law rheology to determine the critical valley angle for the eddies to form. When temperature is incorporated into the ice rheology, the warmer basal ice is less viscous and eddies form in larger valley angles (shallower slopes) than in isothermal ice. We also show that when ice flow is not perpendicular to the valley orientation, complex 3‐D eddies transport ice down the valley. We apply our simulations to the Gamburtsev Subglacial Mountains and solve for the ice flow over radar‐determined topography. These simulations show Moffatt eddies on the order of 100 m tall in the deep subglacial valleys. Key Points: Moffatt eddies likely form and disrupt stratigraphy at the base of ice sheets Observed deep valleys in Gamburtsev Subglacial Mountains likely produce eddies Eddies likely contaminate climate records in ice cores